Nitrogen and truly digestible protein efficiencies of dairy cows fed fresh herbage- or maize forage-based diets: a meta-analysis - M. Ferreira; R. Delagarde; S. Lemosquet; N. Edouard (Animal)
Understanding how dietary forage influences dairy cows’ use of nitrogen (N) and protein resources may help decrease N losses to the environment, which is a major issue in the livestock sector. The present study evaluated the effects of cow and diet characteristics on N use efficiency and the efficiency of truly digestible protein in the intestine (PDI) (i.e., protein use efficiency at the metabolic level), depending on whether the base forage is fresh herbage or maize forage. To this end, a meta-analysis was performed of a dataset composed of 22 experiments that included 266 observations of individual in vivo whole-tract digestibility and N balance for lactating dairy cows fed either fresh herbage diets indoors (Fresh herbage, n = 113) or maize forage diets (Maize, n = 153). The dataset compiled dietary and zootechnical variables such as feed intake, chemical composition of the diet, milk yield (MY), milk composition and cow characteristics. The nutritional value of diets, cow protein requirements and PDI use efficiency were calculated for all diets according to the INRA 2018 feeding system for ruminants. The dataset was then analysed using mixed-effect models, considering the experiment and the cow as random effects. Feed intake, MY and dietary PDI concentration were greater for Maize diets than Fresh herbage diets, while dietary N and energy concentrations were greater for Fresh herbage diets. Dietary N concentration influenced N use efficiency the most, while the ratio of dietary protein concentration to energy concentration influenced PDI efficiency the most. N and PDI use efficiency averaged 23.9 and 72.0%, respectively, for the Fresh herbage diet type, and 30.6 and 74.7%, respectively, for the Maize diet type. This study highlighted that cows use N and PDI in similar ways regardless of whether they are fed fresh herbage or maize diets. In the range of variation studied, each increase in N use efficiency increased PDI use efficiency by the same degree, regardless of the type of diet. This suggests that PDI use efficiency can be predicted from N use efficiency, which is easier to calculate.